Globalized desires. European development and global histories of early modern consumption - Palamar, Jasmin (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Books under review: Beverly Lemire, Global Trade and the Transformation of Consumer Cultures. The Material World Remade, c.1500-1820 (Cambridge 2018). Elif Akçetin and Suraiya Faroqhi (eds.), Living the Good Life. Consumption in the Qing and Ottoman Empires of the Eighteenth Century (Leiden 2018). Frank Trentmann, Empire of Things. How We Became a World of Consumers, from the Fifteenth Century to the Twenty-First (New York 2016).